Mediation Effect of Employee Satisfaction: on Analysis Affecting Intrinsic Motivation on Employee Performance in the Era of the Covid-19 Pandemic (Study at North Lampung Resort Police) - Dyvia Ardianto; Fibria Indriati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims: 1) To determine the effect of intrinsic motivation on job satisfaction: 2) To determine the effect of job satisfaction on performance; 3) To determine the effect of intrinsic motivation on performance; 4) To determine the influence of intrinsic motivation indirectly on employee performance through job satisfaction as an intervening variable. This type of research is descriptive with a quantitative approach. Data was collected by distributing questionnaires to employees and members of the North Lampung Resort Police as many as 96 employees/members using purposive sampling. In this study the independent variable is intrinsic motivation, then the dependent variable is employee performance, while job satisfaction is an intervening variable. The collected data then analyzed using path analysis(pathanalyzing).The findings of this research are: 1) Intrinsic motivation directly has a positive and significant effect on job satisfaction at the North Lampung Resort Police; 2) Job satisfaction directly has a positive and significant effect on employee performance at the North Lampung Resort Police; 3) Intrinsic motivation directly has a significant effect on employee performance at the North Lampung Resort Police; 4) Work motivation indirectly has a significant effect on employee performance through job satisfaction at the North Lampung Resort Police.